Sexual Violence in Italy: Are Women Victims or Responsible? - Adriana Ostuni; Giuseppina Sacco; Pietro Sacco; Alfonso Zizza (European Scientific Journal, ESJ, 2023)
Sexual violence is the imposition of unwanted physical contact obtained by force, manipulation, or coercion. This kind of violence, which is detrimental to the dignity of the person who suffers it, causes deep psychic as well as physical wounds in the victim and is the most widespread violation of human rights in all countries and cultures. This paper tries to investigate whether the stereotype of women being responsible for the sexual violence they suffered is dominant in our society. The study of this stereotype has been addressed through the survey "Gender roles stereotypes and the social image of sexual violence" carried out by ISTAT in 2019 (referred to 2018) on the adult, male, and female, population aged between 18 and 74. With regard to the stereotypes proposed in the survey, the results have shown that there is a clear contrast between young and older women and between women with a higher educational qualification and those with an elementary school degree. At the regional level, however, the contrast is between Central-Northern regions and Southern Italy: in five of the eight regions belonging to the Southern division, the most widespread stereotype is that the responsibility for sexual violence is attributable to women.